Identification of a Cancer Stem Cells Signature of Head and Neck Squamous Cell Carcinoma - Wu, Zeng-Hong; Li, Cheng; Zhang, You-Jing; Zhou, Wen (Frontiers in Genetics, 2022)
Background: Head and neck squamous cell carcinoma (HNSCC) ranking as the sixth most widespread and deadly cancer. In recent times, it has been determined that undifferentiated cell populations with stem cell-like properties in HNSCC are major factors influencing recurrence and progression. Method: In this study, we determine key genes related to stemness by merging WGCNA with HNSCC mRNAsi based on the online database. Results: We first download the mRNA expression-based stemness index (mRNAsi) data and contrast the expression levels of mRNAsi in cancers and control samples and we found significantly elevated mRNAsi expressions in HNSCC tissues (P=0.002). Moreover, the brown module showed a relatively high negative correlation with mRNAsi (cor= -0.8). Thus, we select the brown module as the interesting module and used it for following analysis. We screened 20 key genes including and as to decide the neighbor genes biological interaction network of these 20 stemness-related genes in HNSCC and the top 10 frequent alterations were PIK3CA, FGF3, FGF19, FGF4, DVL3, P3H2, GNB4, COL22A1, COL14A1, and PLOD2. Conclusion: This study showed the critical role of stemness-related genes in HNSCC. However, more related studies are needed to confirm these results.